THE IMPLEMENTATION OF COURSE REVIEW HORAY METHOD THROUGH VIDEO IN IMPROVING SOCIAL SCIENCE LEARNING AT THE FOURTH GRADE STUDENTS OF SDN TANJUNGSARI IN THE ACADEMIC YEAR OF 2014/2015 - hidayah, anis (KALAM CENDEKIA PGSD KEBUMEN, 2018)
Abstract. The Implementation Of Course Review Horay Method Through Video In Improving Social Science Learning At The Fourth Grade Students Of SDN Tanjungsari In The Academic Year Of 2014/2015.The objectives of this research areto describe the steps of Course Review Horay method through video, to improve the achievement of Social Science at the fourth grade students of SDN Tanjungsari in the academic year of 2014/2015, and to describe the problems and solutions.This research was Classroom Action Research. This research was conducted in three cycles consisting of planning, implementation, observation, and reflection. The subjects was all fourth graders of SDN Tanjungsari amounting to 34 students. The results show thatthe implementation of CRH method through video that conducted with appropriate stepscan improve Social Science learning at the fourth grade students of elementary school.  Keywords: course review horay, video, learning, social sciencelearning Abstrak. Penerapan Metode Course Review Horay dengan Media Video dalam Peningkatan Pembelajaran IPS Siswa Kelas IV SDN Tanjungsari Tahun Ajaran 2014/2015. Tujuan penelitian ini adalah untuk mendeskripsikan langkah-langkah penerapan metode Course Review Horay (CRH)dengan media video, meningkatkan hasil belajar IPS pada siswa kelas IV SDN Tanjungsari  tahun ajaran 2014/2015, dan mendeskripsikan kendala dan solusinya. Penelitian ini merupakan penelitian tindakan kelas. Penelitian dilaksanakan dalam tiga siklus yang terdiri dari perencanaan, tindakan, observasi, dan refleksi. Subjek penelitian ini adalah siswa kelas IV SDN Tanjungsari yang berjumlah 34 siswa. Hasil penelitian menunjukkan bahwa penerapan metode CRHdengan media video yang dilaksanakan dengan tepat dapat meningkatkan pembelajaran IPS pada siswa kelas IV SD. Kata kunci: course review horay, media video, pembelajaran, ips